Experience of rituximab therapy in pemphigus: A three-year retrospective study from a Sub-Himalayan State - Ghanshyam Verma; Aditi Sharma; Renu Rattan; Ajeet Negi; Mudita Gupta; Rajni Sharma (Wolters Kluwer Medknow Publications, 2022)
Background: Pemphigus is a group of auto-immune blistering disorders, characterised clinically by mucocutaneous blisters and erosions and histopathologically by intra-epidermal acantholysis. It was traditionally associated with high morbidity and mortality. The use of rituximab has brought upon a new dawn in the treatment of pemphigus. Aim: A retrospective analysis to ascertain the efficacy, tolerance, adverse effect profile, remission, and relapse with the use of rituximab. Material and Methods: A retrospective analysis of all diagnosed pemphigus patients who received rituximab therapy over a period of 3 years was performed. The patient's baseline characteristics, disease duration, clinical presentations, mucosal involvement, disease-severity assessment, and adverse events with rituximab were noted. The outcomes were evaluated based on the definitions of the disease-outcome parameters as early and late endpoints. Results: Of the 17 pemphigus patients, there were 14 females (82.4%) and three males (17.6%) with a mean age of 35.9 ± 16.5 years (range: 9-65 years). Pemphigus vulgaris (PV) was the predominant type in 11 (64.7%) patients. After rituximab infusion, the 17 patients attained the end of consolidation phase (ECP) within 15 days to 3 months, and the mean duration was 1.24 months. The complete remission (CR on/off) ranged from 0.5 to 35 months, and the mean duration of remission was 21.7 months. Within a median time of 4.2 months, almost 80% patients achieved CR on therapy. Nine (53%) patients were in CR without any therapy till the end of the study period, and eight (47%) were in remission while on minimal therapy. Conclusion: Rituximab is an efficacious therapeutic agent for pemphigus and is better tolerated and safer to all the previous medications used in the treatment.